(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the prevalence of HBV and HCV infections in hemodialysis patients living in the province of Sindh. Study Design: Observational study Place and Duration of Study: This study was conducted at the multiple district level centers hospital Karachi from January 2017 to December 2018. Materials and Methods: 251 patients with hemodialysis were enrolled to study. Patients who were on maintenance haemodialysis treatment for more than 6 months, 3 times a week, for 4 hours per session, with the dialysis dose being mediated by ionic conductivity Kt/V>1.5, and with an the age between 18-80 years were included in study. Results: Out of 251 patients, 52.6% were male and 47.4% were female. The mean age of patient was 51.47±12.81 years. Mean hemodialysis duration was 6.51±6.96 years. 13.1% were presented with upper GI bleeding, 10.4% with hepatic encephalopathy, 7.2% with malena and 15.5% with ascites. We found 12.4% patients with hepatitis B and 22.3% with hepatitis C. significant association of hepatitis B and hepatitis C with age group and gender. Conclusion: This study has shown that the patients on maintenance hemodialysis have a high prevalence of HCV and HBV infection and a due to exposure of several different risk factors such as improper handling of the needles, careless behaviour towards the importance of vaccination against the virus and using multiple centres for dialysis at a time.